A Sustainable Islamic Educational Service Model for Enhancing Stakeholder Satisfaction in Madrasah - Sulaiha Annisyaroh; Muhammad Walid; Indah Aminatuz Zuhriyah (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Madrasah education in regional Indonesia faces a structural tension that conventional service quality frameworks have not adequately addressed. Quality is measured by what happens inside the institution, yet stakeholder satisfaction is shaped substantially by what happens outside its walls, particularly the geographic and economic conditions that determine whether students can reach the school at all. This study investigates how MTsN 1 Sampang, a public Islamic junior secondary school in the Madura archipelago, responds to this tension through an accessibility-based service innovation grounded in Islamic ethical values. A convergent parallel mixed-method design was applied through a case study framework, drawing on a survey of 100 stakeholders selected through proportional stratified random sampling, in-depth interviews with 15 key informants, participant observation across 24 working days, and the analysis of 47 institutional documents. The instrument was tested through Confirmatory Factor Analysis, yielding an Average Variance Extracted of 0.623 and a Cronbach's Alpha of 0.924. Findings reveal that stakeholder satisfaction reached 90.4 percent, with Accessibility Orientation (r = 0.724) and Islamic Service Values (r = 0.689) emerging as stronger predictors than the five classical SERVQUAL dimensions. The shuttle program produced a 21.7 percentage point reduction in tardiness and an 81.8 percent decline in dropout rates over three years. The study formulates the ABIES Model (Access-Based Islamic Excellent Service), validated through a two-round Delphi technique with a Kendall's coefficient of concordance of 0.82, repositioning accessibility as a primary determinant of madrasah service quality rather than a precondition for it.